CULTURE SHOCKS FACED BY FORIEGN STUDENTS AT ANTASARI STATE ISLAMIC UNIVERSITY BANJARMASIN - Nur Laila Kadariyah; Nur Faizah Hayati (LET: Linguistics, Literature and English Teaching Journal)
This research describes the culture shock faced by the foreign students who study at Antasari State Islamic University Banjarmasin. Foreign students who are conscientious in this research are 7 students come from Turkey and one from Thailand. The objectives of this research are: (1) To find out the culture shocks faced by the foreign students in academic aspects; (2) To find culture shocks faced by the foreign students in social aspects. All of the data have analized by descriptive and qualitative research. The results of this research indicated that the foreign students faced culture shock in academic aspects  that consist of (1) In institutional rules: the complicated and long of procedures filling Study Plan Sheet Online, collecting of Study Plan Sheet, registrating of courses (2) The cleanliness of the university environment (3) Lecturers’ Rules which consists of discipline on the schedule the lectures, the use of local language (Banjarese) in the classes wether by lecturers or local students. Then, culture shocks in Social Aspects students faced the behavior and attitude of the local students such as talking and made jokes while lecturing, using handphones while lecturing, spitting anywhere, male and female local students’ interaction, and   the system of local public transportation.